2014
DOI: 10.1093/neuonc/not242
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 inhibition delays growth of neurofibromatosis type 2 schwannoma

Abstract: Taken together, these results constitute definitive evidence that justifies proceeding with clinical trials using mTORC1-targeted agents in selected patients with NF2 and in patients with NF2-related sporadic tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 45 publications
4
56
0
Order By: Relevance
“…4) [24]. This is in line with our observation in schwannoma mouse model, where a small increase in phospho-AKT seen under rapamycin treatment normalized after treatment discontinuation [15]. The three VS exhibited marked elevated S6 phosphorylation as observed in our mouse schwannoma model, where tumor growth inhibition was dependent on continuous exposure to rapamycin, with S6 phosphorylation re-expression after rapamycin withdrawal.…”
Section: Tumor Tissue Biomarker Evaluationsupporting
confidence: 89%
See 3 more Smart Citations
“…4) [24]. This is in line with our observation in schwannoma mouse model, where a small increase in phospho-AKT seen under rapamycin treatment normalized after treatment discontinuation [15]. The three VS exhibited marked elevated S6 phosphorylation as observed in our mouse schwannoma model, where tumor growth inhibition was dependent on continuous exposure to rapamycin, with S6 phosphorylation re-expression after rapamycin withdrawal.…”
Section: Tumor Tissue Biomarker Evaluationsupporting
confidence: 89%
“…3). As previously reported in an index NF2 patient treated with rapamycin [15], a concentrationdependent response was observed. Everolimus blood trough levels were higher in stable patients than in progressive patients (median 22.7 lg/mL (IQR 16.5-30.2) versus 10.6 (IQR 9.7-15.5), P = 0.03 Mann-Whitney test).…”
Section: Radiological Evaluation Of Drug Activitysupporting
confidence: 84%
See 2 more Smart Citations
“…The volume calculation algorithm in OsiriX was used to obtain a threedimensional tumor volumetric measurement (mm 3 ) complex region, using the SC4-9 cell line. SC4-9 has become a standard model in NF2 research since it recapitulates signalling network signatures of human and mouse NF2 schwannomas [19,21,25,26], with high grafting efficiency when orthotopically injected into the sciatic nerves of immunodeficient NU/NU mice [34]. We found that the microsurgical approach successfully targeted the anatomic location where human VS predominantly arise and tumor development could be monitored by in vivo imaging.…”
Section: Discussionmentioning
confidence: 88%